2019
DOI: 10.1103/physrevd.100.025007
|View full text |Cite
|
Sign up to set email alerts
|

Two-mode Gaussian quantum states measured by collinearly and noncollinearly accelerating observers

Abstract: We generalize 1 + 1-dimensional formalism derived by Ahmadi et. al. [Phys. Rev. D 93, 124031] to investigate an effect of relativistic acceleration on localized two-mode Gaussian quantum states in 3 + 1-dimensional spacetime. The following framework is then used to analyze entanglement of the Minkowski vacuum as witnessed by two accelerating observers that move either collinearly or noncollinearly. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Therefore, the behavior of entanglement harvesting therein would be an interesting topic, since it is expected to be affected by both the presence of the boundary and the accelerated motion of the detectors which is connected the Unruh effect. Indeed, on one hand, a lot of studies have revealed the influence of acceleration on quantum entanglement via various detector models, including two-level detectors or UDW models [17,33], harmonic oscillators [37,38], and wave packets [39,40]. In particular, it was argued in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the behavior of entanglement harvesting therein would be an interesting topic, since it is expected to be affected by both the presence of the boundary and the accelerated motion of the detectors which is connected the Unruh effect. Indeed, on one hand, a lot of studies have revealed the influence of acceleration on quantum entanglement via various detector models, including two-level detectors or UDW models [17,33], harmonic oscillators [37,38], and wave packets [39,40]. In particular, it was argued in ref.…”
Section: Introductionmentioning
confidence: 99%
“…1), each accelerating with identical proper acceleration A. Although the scheme discussed in [46] involves only 1 + 1 dimensional spacetime, a generalization to the higher dimensional case discussed in [47] is straightforward. The initial state spanned by three modes of the inertial observer is prepared in such a way that it can be also detected by three accelerating observers.…”
Section: A Gaussian Channelmentioning
confidence: 99%
“…It follows from the assumption of equal accelerations. The particular values of the mode overlaps α and β depend on the choice of mode functions and we stick to the ones used previously in [44][45][46][47]. For such a choice, β coefficients are at least 8 orders of magnitude smaller than α's and can be safely neglected.…”
Section: A Gaussian Channelmentioning
confidence: 99%
See 2 more Smart Citations